Effect of chronic N deposition on soil carbon composition along a subtropical urbanization gradient: Underlying microbial taxa with ecological roles - Wenjuan Yu; Xinyu Jiao; Yan Li; Shanshan Zhang; Hongzhang Kang (Geoderma)
Contributions of plant- vs. microbial-derived C to soil organic carbon (SOC) is vital for predicting SOC persistence, yet little is known about impact of N deposition on SOC composition and the underlying microbial taxa with distinct ecological roles in subtropical forests. Here, along an urbanization gradient with increasing ambient N deposition from exurb and suburb to center in Shanghai, we investigated relationships among SOC composition and N deposition and uncovered the microbial mechanisms. SOC composition reflected by 121 pyrolysis products were related to soil physicochemical and microbial variables. Lignin (plant-derived SOC) and N-bearing (microbial-derived SOC) abundances showed opposite patterns and relationships with biogeochemical variables along the gradient. Ratio of lignin to N-bearing increased from exurb and suburb to center and had strong positive relationships with soil available N and SOC. This suggests that N deposition caused a greater increase in plant- vs. microbial-derived SOC. Major bacterial and fungal taxa positively related to the ratio and lignin abundance were involved in partial decomposition of lignin. Taxa positively related to the ratio and negatively to N-bearing abundance were copiotrophic while those showing opposite relationships were oligotrophic. These major taxa were also correlated with SOC and/or available N. Overall, our study uncovered microbial taxa with distinct ecological roles underlying effect of N deposition on SOC composition in subtropical forests.